MENGEMBANGKAN MINAT PESERTA DIDIK DALAM PEMBELAJARAN IPAS MELALUI MODEL INQUIRY PADA SD INPRES BUMI SAGU KOTA PALU. - Andi mursyidin mubaraq; Supriyatman (STKIP Subang, 2025)
This research was motivated by the low learning interest of students in Science and Social Studies (IPAS) at grade V of SD Inpres Bumi Sagu, Palu. Observations revealed that most students showed a lack of interest in the subject, were passive during discussions, and rarely asked questions. The aim of this study was to improve students' learning interest through the implementation of the inquiry learning model. The research employed a Classroom Action Research (CAR) method conducted in two cycles. The subjects were 16 students, with the researcher also acting as the classroom teacher. Data collection techniques included observation, learning interest questionnaires, and documentation. The results showed that the application of the inquiry model significantly increased students’ learning interest. In the first cycle, most students were categorized as having moderate interest, while in the second cycle, the majority (87.5%) demonstrated a high level of learning interest. The inquiry model effectively promoted student engagement, fostered curiosity, and created a more meaningful learning environment. Therefore, inquiry is considered an effective alternative learning model to enhance students' interest in learning at the elementary level.